2008
DOI: 10.1002/jsfa.3384
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic diterpene and α‐tocopherol contents in leaf extracts of 60 Salvia species

Abstract: BACKGROUND: Carnosic acid and carnosol, the two major phenolic diterpenes present in rosemary and sage extracts, have received attention in food science and biomedicine because of their potent antioxidant properties. In plants, these compounds have been identified as being present in some species of the family Lamiaceae, but there is still little information about their distribution within the plant kingdom. The aim of the present study was to gain a better understanding of the occurrence of these compounds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
(26 reference statements)
4
41
1
Order By: Relevance
“…The main sage antioxidants are rosmarinic acid, carnosic acid, and α-tocopherol. While the α-tocopherol content is more or less similar in different herb species and varieties, the carnosic acid content can differ by a factor of up to twenty (Abreu et al 2008). This can be the explanation of the differences between our values and the published data.…”
Section: Determination Of Antioxidant Capacity Of Extractscontrasting
confidence: 46%
“…The main sage antioxidants are rosmarinic acid, carnosic acid, and α-tocopherol. While the α-tocopherol content is more or less similar in different herb species and varieties, the carnosic acid content can differ by a factor of up to twenty (Abreu et al 2008). This can be the explanation of the differences between our values and the published data.…”
Section: Determination Of Antioxidant Capacity Of Extractscontrasting
confidence: 46%
“…The isolated compounds were identified by their NMR and MS spectral analysis as four diterpenes: rosmadial ( I ) (Nakatani & Inatani 1983), carnosol ( II ) (Abreu et al 2008), 16-hydroxycarnosol ( III ) (Luis, Lahlou, Andrés, Sood, et al 1996), sageone ( IV ) (Tada et al 1994); two flavonoids: cirsimaritin ( V ) (Wang et al 2004), salvigenin ( VI ) (Ayatollahii et al 2009); and three triterpenes: oleanolic acid ( VII ) (Pettit et al 1966; Martins et al 2013), uvaol (3β,28-dihydroxy-urs-12-ene) ( VIII ) (Lee et al 2013), ursolic acid ( IX ) (Pettit et al 1966; Silva et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…The plant is used for diaphoretic and diuretic effects (Dentali & Hoffmann 1990). Previous to our research, several compounds including flavonoids, mono-, sesqui-, di- and tri terpenes, have been already identified and/or isolated from S. apiana (Pettit et al 1966; González et al 1992; Luis, Lahlou, & Andrés 1996; Luis, Lahlou, Andrés, Sood, et al 1996; Dentali & Hoffmann 1990; Borek et al 2006; Abreu et al 2008; Takeoka et al 2010). However, this plant has not been studied for cannabinoid or opioid receptors activity.…”
Section: Introductionmentioning
confidence: 99%
“…Naïve populations of N. bryanti prefer to feed on plants that largely contain low-molecular-weight PSCs (Abreu et al, 2008;Atsatt and Ingram, 1983;Stintzing and Carle, 2005) that are unlikely to inhibit digestive enzymes. However, coastal live oak (Quercus agrifolia), which is rich in phenolics and tannins, also grows within the native habitat of naïve N. bryanti (Atsatt and Ingram, 1983).…”
Section: Functional Implicationsmentioning
confidence: 99%
“…These populations vary in the types of PSCs they encounter in the wild. The naïve population feeds mainly on plants that produce lowmolecular-weight defense compounds that are unlikely to bind dietary or enzymatic proteins (Abreu et al, 2008;Atsatt and Ingram, 1983;Stintzing and Carle, 2005). Alternatively, creosote bush leaves produce a complex resin consisting of various phenolics, flavonoids and saponins (Mabry et al, 1977), chemical classes that have been shown to bind and inhibit digestive enzymes (Cheeke, 1971;Fontana Pereira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%